MRO- CHA a hub for MRU indigenous people promoting the MRU: retaining their ethnicity - Saifee, Kazi Sumaiya (BRAC University, 2014)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Architecture in Architecture, 2013.